Keunggulan Mobile Based Assesment Dengan Google Form di Masa Pandemi Oleh Mahasiswa PPG - Sibua, Sulami; Amiroh, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research was conducted with the aim and hope of revealing the advantages of using mobile based assessment media with google form by PPG Phase I students at Khairun University. So that there are more efforts made by education actors so that learning starts from the process until the results can be as expected, even with the limitations of the current pandemic conditions. The results of the research, data analysis shows that there are advantages of the google form that can be used in the assessment, namely 1) easy to access and operate, 2) facilitate teachers in making questions, 3). facilitate teachers in assessing student work, and 4) efficient in the process and results. However, there are still a few weaknesses where the assessment of student work in the form of essay questions cannot be done automatically, and there is still a lack of features on the google form. Anticipating the invalidity of the assessment results because there is a tendency to cheat, various steps are taken by the teacher including using the random question feature, limiting the time for processing questions, avoiding copypasting questions from the internet, setting the feature to only answer once, and no less important is instilling the importance of honesty in students. Conclusion, Based on the results and discussion, it can be concluded that the mobile based assessment with google form is very well done for students at school, although there are some weaknesses according to the results of the study. Keywords: Google form, Mobile based assessment, Assessment